The role of institutional factors on the regional innovation culture in startup hubs - A comparison between the capital cities Berlin & Tel Aviv - Novak, Daniela; Štěrbová, Ludmila, 1957-; Antonovic, Vladan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
In a currently changing global business environment, this thesis aims to underline the importance of driving and influencing factors of regional innovation culture. Although existing literature outlines underlying theories, there has been little investigation using qualitative data into how less visible institutional factors impact regional innovation culture. This thesis uses qualitative social research based on semi structured interviews. Elements of this analysis include soft attributes, such as cultural diversity, entrepreneurial thinking and openness, as well as the role of hard factors, such as monetary incentives, and how effective they are in forming a region’s innovation culture. The current state of regional innovation culture in Berlin and Tel Aviv in terms of the defined hypotheses is satisfactory and complementary towards global innovation indices. Besides measurable indicators such as venture capital investments and patent registrations, little research has been dedicated to less visible elements influencing regional innovation culture. Special attention is drawn to successful regions in terms of innovation through institutional factors and offers guidance and suggestions for stimulating innovative activities in less developed regions in the future
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses